2005
DOI: 10.1002/14651858.cd004649.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Laxatives for the treatment of hemorrhoids.

Abstract: The use of fiber shows a consistent beneficial effect for relieving overall symptoms and bleeding in the treatment of symptomatic hemorrhoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
12

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 26 publications
1
32
0
12
Order By: Relevance
“…Several studies have already done hemorrhoidal diseases and anal fissures during pregnancy. In one study in Spain by 'Alonso Coello' et al on the effect of laxatives during pregnancy in seven subjects, it was shown that fiber could decrease the hemorrhoidal symptoms and bleeding (7). In another study in France in women during pregnancy until delivery, anal fissure was visible in 15.2% of the subjects and hemorrhoidal diseases in 20% (14).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies have already done hemorrhoidal diseases and anal fissures during pregnancy. In one study in Spain by 'Alonso Coello' et al on the effect of laxatives during pregnancy in seven subjects, it was shown that fiber could decrease the hemorrhoidal symptoms and bleeding (7). In another study in France in women during pregnancy until delivery, anal fissure was visible in 15.2% of the subjects and hemorrhoidal diseases in 20% (14).…”
Section: Discussionmentioning
confidence: 98%
“…Constipation in pregnancy results from a change in diet, a decline in physical activity, hormonal alterations, and a decrease in digestive system function (5,6). In different studies, the prevalence of anorectal diseases (hemorrhoidal diseases and anal fissure) and constipation in the third gestational period was reported 11% to 38% (2,5).Thus, using therapeutic measures without any side effects for the patients and the fetus are clinically important (7) . Recently, the use of some herbal medicines like flovonoic acid extracted from the citrous has been taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Não há evidência de benefício para dor ou prurido como sintomas isolados. 10 No mercado brasileiro, existem medicamentos à base de Plantago ovata e Plantago psyllium. A Relação de Medicamentos Essenciais (Rename) traz Plantago ovata para constipação e síndrome do intestino irritável, mas não menciona o uso para doença hemorroidária.…”
Section: Contextualização Ao Cenário De Prática Da Aps E Medicina De unclassified
“…6 Os sintomas mais comuns são sangramento, prolapso, prurido, dor ou desconforto anal e, menos frequentemente, exsudação perianal. 1,6,7,10 A doença hemorroidária, em sua classificação mais utilizada, pode ser interna, externa ou mista, de acordo com a localização do mamilo hemorroidário no canal anal, conforme descrito previamente. A fim de guiar a terapêutica mais adequada, Banov et al 11 propuseram classificar a forma interna com base no grau de prolapso e sangramento em a) Grau I: quando há sangramento, porém não prolaba abaixo da linha pectínea aos esforços ou evacuação; b) Grau II: quando prolaba abaixo da linha pectínea, ao esforço evacuatório, com prolapso pelo ânus, porém retraindo espontaneamente após cessado o esforço; c) Grau III: quando prolaba à evacuação e/ou aos esforços, com prolapso pelo ânus, porém sem retração espontânea, sendo necessário redução digital; e d) Grau IV: quando o prolapso é irredutível e o mamilo hemorroidário permanece permanentemente prolabado.…”
Section: Introductionunclassified
See 1 more Smart Citation